Intervenção pedagógica com jogos concretos e eletrônicos para a construção de estruturas cognitivas: um estudo piagetiano - Gonçalves, Érica de Cássia [UNESP] (2020)
In the current context, the process of accelerating technologies, especially those related to communication, has influenced the paradigm shifts on the way of thinking about society and its institutions, thus impacting the social and cultural life of human beings. It is not difficult to see that one of the changes that has occurred in recent times is the way children currently play and interact with each other, since since early childhood contact with mobile and portable devices has been part of their hobby, replacing many times of outdoor play, social interaction, use and exploration of concrete games, among others, by games on the screen. For this reason, it is natural for discussions and reflections to be encouraged about the impacts of such changes on society as a whole and, mainly, on the development of children. This research, which is part of a series of investigations that have been carried out in GEADEC - Group of Studies and Research in Learning and Development in the Constructivist Perspective, aimed to investigate the effects of technology in the construction of intelligence structures in the light Piaget's theory, comparing pedagogical interventions performed with concrete games and interventions with the same games, in electronic versions. For this, the work methodology consisted of a quasi-experimental design study, with pre and post-tests and an intervention period, where the subjects were submitted to the operational tests of conservation of the discrete quantities (cards), inclusion of classes (flowers ) and serialization (rods). The construction of the infralogical structures of space was also evaluated by means of proof of the copy of geometric figures (topological space), projective line (projective space) and horizontal and vertical coordinates (Euclidean space). The research participants were 38 students from municipal schools in a city in the interior of Minas Gerais, aged between 7 and 10 years old, who had not yet built the operational thinking structures in the pre-test, distributed in three groups, two experimental (G1 and G2) and a control group (CG). In G1, there was pedagogical intervention using electronic games; in G2 there was intervention with the same games, however, in the concrete versions and in the control group (CG), there was no intervention. The interventions took place individually, in pairs or in small groups, according to age, twice a week, in sessions of 1 hour each, for a period of 3 months. In total, there were 19 sessions with the games Kalah, Cilada, Lig 4, O Quarto and Velha in 3D. The hypothesis that permeated this study was that the pedagogical intervention would be favorable to the construction of the logical structures of the operative thinking in both groups, but there would be a difference in the construction of the infra-logical structures of space of subjects who would participate in the GE1 (electronic), since, when using electronic games, some concrete actions that allow exploring the properties of objects would be more difficult to occur. The results indicated differences in the exploration of the materials and rules of the game, in the practice and construction of strategies and in the resolution of problems, from the plays between the subjects who participated in the intervention with concrete games and those who participated in the intervention with the same games, in the electronic version. In addition, in the post-test it was found that there was a qualitative and quantitative change in the thought structures evaluated in a more expressive way between the subjects of the experimental groups compared to the control group, as well as there was also a difference in the performance of the subjects of the groups. after the intervention period. Such difference was more significant in the result of the tests related to the notion of space, where GE2 (concrete) performed better than GE1 (electronic), showing that electronic 11 games can even be useful to develop a job, with pedagogical intervention, but they do not substitute the concretes in several aspects because they do not guarantee essential principles, which, according to Piaget's theory, explain development.